Complex spine deformities in young patients with severe osteogenesis imperfecta: Current concepts review. (February 2019) - Castelein, R. M.; Hasler, C.; Helenius, I.; Ovadia, D.; Yazici, M.; ,
Abstract: The severity of osteogenesis imperfecta (OI), the associated reduced quality and quantity of collagen type I, the degree of bone fragility, ligamentous laxity, vertebral fractures and multilevel vertebral deformities all impair the mechanical integrity of the whole spinal architecture and relate to the high prevalence of progressive kyphoscoliotic deformities during growth. Bisphosphonate therapy may at best slow down curve progression but does not seem to lower the prevalence of deformities or the incidence of surgery. Brace treatment is problematic due to pre-existing chest wall deformities, stiffness of the curve and the brittleness of the ribs which limit transfer of corrective forces from the brace shell to the spine. Progressive curves entail loss of balance, chest deformities, pain and compromise of pulmonary function and eventually require surgical stabilization, usually around puberty. Severe vertebral deformities including deformed, small pedicles, highly brittle bones and chest deformities, short deformed trunks and associated issues like C-spine and cranial base abnormalities (basilar impressions, cervical kyphosis) as well as deformed lower and upper extremities are posing multiple peri- and intraoperative challenges. Hence, an early multidisciplinary approach (anaesthetist, pulmonologist, paediatric orthopaedic spine surgeon) is mandatory. This paper was written under the guidance of the Spine Study Group of the European Paediatric Orthopaedic Society. It highlights the most pertinent information given in the current literature and various practical aspects on surgical care of spine deformities in young OI patients based on the personal experience of the contributing authors.